Age at Diagnosis and Breast Cancer Survival in Iran - Fatemeh Asadzadeh Vostakolaei; Mireille J. M. Broeders; Nematollah Rostami; Jos A. A. M. van Dijck; Ton Feuth; Lambertus A. L. M. Kiemeney; André L. M. Verbeek (International Journal of Breast Cancer)
Background. Tumour characteristics are the most important prognostic factors in breast cancer. Patient-related factors such as young age at diagnosis, obesity, and smoking behaviour may also modify disease outcome. Due to the absence of a unique definition for “young age breast cancer” and the resulting variation in disease management, findings on the association between young age and prognosis of breast cancer are controversial. Methods. This study included 1500 patients with a primary diagnosis of breast cancer in six Iranian hospitals from 5 provinces. We modelled the relative excess risk (RER) of breast cancer death to age at diagnosis and tumour characteristics. Results. Excess risks of death were observed for stage IV disease and poorly differentiated tumours: RER of 4.3 (95% CI: 1.05–17.65) and 3.4 (95% CI: 1.17–9.87), respectively. “Older” patients, particularly those aged 50 and over, presented more often with advanced and poorly differentiated tumours (P=0.001). After adjustment for stage, histological grade, Her-2 expression, estrogen and progesterone receptors, and place of residency, breast cancer mortality was not significantly different across age groups. Conclusion. We conclude that there is no prognostic effect of age at diagnosis of breast cancer among breast cancer patients treated at cancer centres in different parts of Iran; young and relatively old women have similar risks of dying from breast cancer.